Are secondary cities in Asia and Africa ready for food systems transformation? Policy insights from Bangladesh, Kenya, Rwanda, and the Philippines - Daniel Gacutan Salunga; Kaspar Wyss (Frontiers in Public Health, 2026)
Background Policies are essential tools for food systems transformation to reshape production, distribution, and consumption; enabling sustainable, healthy, and equitable outcomes and simultaneously address malnutrition, climate change, and social inequalities. This systematic policy mapping and content analysis aimed to synthesize available nutrition and food systems policies and action plans in secondary cities in Bangladesh, Kenya, Rwanda, and the Philippines, describing characteristics, types, thematic and food value chain focus, and food security and nutrition outcomes. Methods In 2024 and 2025 documents were systematically collected across eight cities in four countries through formal and informal channels. 89 documents dated from January 2015 to 2025 were assembled and underwent eight steps of systematic policy mapping and content analysis following the food systems framework. Results Thirty-six screened documents met eligibility criteria and were included in the analysis. Nutrition governance and interventions are the focus of most policies. Cities differ in priorities. Gaps exist on the food value chain relating to storage, transport and trade, and processing and transformation. For outcomes, healthy diets emerged as the primary area of focus while food stability is the least addressed. Limited measures to manage shocks and seasonal volatility were seen. Conclusion Addressing policy gaps in the food value chain and improving measures for food stability is essential. Strengthening policy foundation through multisectoral engagement and evidence-based governance is key. Future studies should examine implementation of key policies and action plans at the local level.